Effect of food on orally-ingested titanium dioxide and zinc oxide nanoparticle behaviors in simulated digestive tract. (April 2021) - Zhou, Pengfei; Guo, Mengfan; Cui, Xinyi
Abstract: Nanomaterials have been widely utilized in human daily life. The interaction between nanoparticles (NPs) and food matrices through oral ingestion is important for fate and potential toxicity of NPs. In this study, the interaction between NPs (i.e., titanium dioxide (TiO2 ) and zinc oxide (ZnO)) and food matrices (namely sucrose, protein powder, and corn oil) was investigated by use of an in vitro physiological model. Measurement using asymmetrical flow field-flow fractionation (AF4 ) showed that particle size of TiO2 NPs in saliva fluid decreased from 102 ± 6.21 nm (control) to 69.2 ± 6.90 and 81.9 ± 4.30 nm in protein powder and corn oil. Similar trend was also observed for ZnO. Compared with gastric fluid, micelles formed by corn oil in intestinal fluid further dispersed NPs, as indicated by approximately 11.1% and 13.2% decrease in particle size of TiO2 and ZnO NPs, respectively. Characterization of TEM, FTIR and AFM showed that a layer of biological corona was attached on surface of NPs in protein and oil. The XPS demonstrated that oil bound with NPs through forming covalent bonds, while protein bound with NPs through van der Waals force and electrostatic force for TiO2 and ZnO NPs, respectively. The result here demonstrated the importance of considering food effect when investigating the morphology and behavior of NPs after oral ingestion. This understanding was valuable in assessment of environmental fate and biological effects of NPs. Graphical abstract: Image 1 Highlights: Behaviors of TiO2 and ZnO nanoparticles (NPs) in digestive tract were investigated under the influence of food. Protein and oil significantly decreased NP particle size in saliva, and oil dispersed NPs in intestinal fluid due to micelle. AF4 -MALS was more suitable for analysis of NP particle size in complex matrices compared with DLS and SEM. Oil bound with NPs through covalent bonds, while protein through van der Waals force and electrostatic force.